2016
DOI: 10.5897/ajb2016.15559
|View full text |Cite
|
Sign up to set email alerts
|

Coating with fungicide and different doses of fertilizer in vinhatico seeds

Abstract: Plathymenia reticulata Benth occurs in open formations of the Brazilian Cerrado and Atlantic Forest. The seeds are affected by pathogens that reduce germination. The use of fungicides is defined for many species, but, for forest species, further studies are necessary. Thus, the aim of this study was to evaluate and identify the physical and physiological quality of mahogany seeds that are coated with fertilizer and fungicide. The treatments were: seed coating with sand + lime + fungicide with different doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The use of the temperature of 40˚C was also efficient in drying coated seeds of Stylosanthes, perennial soybean, and Persea indica [11] [18] [19], which reinforces the effectiveness of this seed-coating method.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The use of the temperature of 40˚C was also efficient in drying coated seeds of Stylosanthes, perennial soybean, and Persea indica [11] [18] [19], which reinforces the effectiveness of this seed-coating method.…”
Section: Resultsmentioning
confidence: 92%
“…The authors observed increases of 100% to 150%, respectively, in TSW, when these materials were added. Likewise, [19] observed increases of up to 100% in the TSW of Persea indica as they increased the doses of NPK fertilizer added to the filler with sand and limestone. According to [11], the texture of limestone and sand favor the formation of a structure with more granules around the seed, which consequently increases its mass.…”
Section: Resultsmentioning
confidence: 99%
“…For seed coating, we used, as filling material, sand + limestone [9] and increasing doses of fertilizer NPK 4-14-7 + boron and zinc, being the following treatments: T1: sand + limestone; T2: sand + limestone + 25 g of fertilizer (mixture of N-P-K + boron and zinc); T3: sand + limestone + 50 g of fertilizer; T4:…”
Section: Methodsmentioning
confidence: 99%